Investigating clinically relevant phenotypes of neurodevelopmental copy number variants in Children and Adults - Foley, Claire (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2021)
Background: Neurodevelopmental copy number variants (ND CNVs) present with clinically pleiotropic effects, transcending psychiatric diagnostic borders. Gaining clarity on the neurodevelopmental and psychiatric phenotypic effects ofND CNVs in different populations is essential to providing clinically relevant information and services to carriers. Aims and structure of thesis: The central aim of this thesis was to investigate the relationship between psychiatric and neurodevelopmental phenotypes and ND CNV carrier status to inform our understanding of ND CNV phenotypes and provide clinically translatable insights. Existing datasets were leveraged for secondary data analysis of large cohorts of previously understudied populations. Chapter 1 discusses findings in the literature supporting the exploration of psychiatric and neurodevelopmental phenotypes associated with ND CNVs in relevant populations. Chapter 2 describes an analysis of psychiatric risk outcomes associated with ND CNV carrier status in a cohort of youths with ASD and explores the moderating effect of sex on specific outcomes. A follow up analysis is conducted in a sample of ASD-unaffected siblings, to explore identified associations between ND CNV carriers and psychopathology in the absence of ASD. Chapter 3 presents an investigation of psychiatric risk outcomes associated with ND CNVs in a large clinical cohort of youths and examines for a moderating effect of sex in specific outcomes. The effect of NDDcomorbidity in the relationship between ND CNVs and psychopathology is explored for relevant outcomes. Chapter 4 describes an analysis investigating the utility of psychiatric and neurodevelopmental phenotypic features in modelling ND CNV carrier status in individuals with schizophrenia. Data are presented from a discovery and replication cohort. Finally, Chapter 5 presents a general discussion of the findings. Results: The analysis of the association between psychiatric phenotypes and ND CNVs in youths with ASD revealed an interaction of between sex and ND CNV status on risk of affective problems. Females with an ND CNV were significantly more likely to present with depressive symptoms than males with or without an ND CNV. NDCNV status was significantly associated with increased risk of affective problems in the sample of typically developing siblings; this effect was driven by female carriers of ND CNVs only. The analysis of the association between psychiatric symptoms and ND CNVs in a large clinical cohort of youths showed an increased risk of subclinical psychotic symptoms in youths with ND CNVs. This association was also present when individuals with an ASD diagnosis or significant cognitive deficits were excluded, indicating that the association was independent of neurodevelopmental comorbidity in this sample. In adults with schizophrenia three phenotypic variables (specific learning disorder, developmental delay, and comorbid neurodevelopmental disorder) were significant in modelling positive carrier status for schizophrenia associated CNV. Replication analysis in a separate cohort confirmed developmental delay and comorbid neurodevelopmental disorder as significant predictors of positive carrier status for schizophrenia associatedCNV status. Conclusion: The results from this work provide novel, clinically relevant insights into neurodevelopmental and psychiatric associations with ND CNVs in previously understudied populations. An improved understanding of psychiatric and neurodevelopmental phenotypes associated with ND CNVs can inform genetic testing and counselling and may help with monitoring risks, prevention strategies and early intervention for ND CNV carriers.
APPROVED
Keywords: Psychiatry; Neuropsychiatric genetics; Neurodevelopmental phenotypes; Genetics; Copy number variants